Peripheral giant cell granuloma of maxilla - Nilima Sharma; Safia Rana; Sujata Jetley (Wolters Kluwer Medknow Publications, 2022)
It is often documented that chronic irritation could be an etiology of oral cancer; yet out of negligence little heed is paid to any sort of discomfort until it grows to a sizable mass where it is difficult to go unnoticed. Intraorally, the source of irritation could vary from a jagged tooth edge to a chronic cheek bite. Furthermore, the removable prosthesis and orthodontic appliances can lead to alteration of the oral mucosal tissue. This case report represents one such sequelae of an ill-fitting dental prosthesis. Surprisingly and unfortunately, the broken denture was still in use by the patient until the damage caused by it could no further be ignored, it is then that the patient sought medical help. A histopathological diagnosis of reparative giant cell granuloma was made, and the patient was treated by successful excision of the same.